Adolescent delinquency and sexual deviations - A case study at the Re-education Center in Jijel - BEN NASR, Haroun; KOUIDRI, Ali (Social Sciences Journal, 2024)
This study aims to detect some of the different sexual deviations found in adolescent delinquents who are in reeducation centers, we chose the clinical method as a study method, and we used the network of clinical observation and clinical interview semi-directive as study tools for research’s purpose to reach scientific results. The research sample included 5 teenagers in the specialized reeducation center in Jijel province, But we will only address one case and we will symbolize it with the letter "A" and the results obtained showed that "A" is suffering of a fundamental sexual deviation that is sadism, and a disguised sexual deviation represented in sexual orientation to children that we predict it will develop to pedophilia in the future if it won’t be taken care of. Keywords: adolescence, delinquency, sexual deviations.